Long Term Flux of Saharan Dust to the Aegean Sea around the Attica Region, Greece - Vasilatou, Vasiliki; Manousakas, Manousos; Gini, Maria; Diapouli, Evangelia; Scoullos, Michael; Eleftheriadis, Konstantinos (Frontiers in Marine Science, 2017)
In this study, Particulate Matter (PM) samples, collected during two summer and two winter months over a long-term period (1984-2012) at a suburban site in Athens (Greece), were used in order to examine the connection between Sahara dust long range transport events and mass concentrations of the aerosol mineral component, as well as the relative abundance of specific crustal components. As a result, the average deposition flux of dust to the Aegean Sea around the Attica Region, during days with Sahara dust transport events, was calculated. The elemental concentration of aerosol samples was determined by means of ET-AAS, ED-XRF. Mineral dust was chemically reconstructed by using the elemental concentrations of the crustal species based on their common oxides. Two different air mass transport models (HYSPLIT and FLEXTRA) were used for the identification of the days with dust transport events. Τhe dust deposition velocity of the particles was calculated by using Stokes drag law, while the dust deposition flux was calculated taking into account the mean particle size of the aerosol coarse size fraction, which is dominated by the transported crustal component during Sahara dust intrusions. The mineral dust contribution was higher in summer, when dry weather conditions prevail. The Ca/Fe ratio was examined for all years, since this ratio is often used for the identification of Saharan dust events. For the years 1996 and 1998 the Ca/Fe ratio indicates an influence by local urban generated dust. The dust deposition flux per day of a Sahara intrusion event varied from 61 –199 μg/m2 with an average value of 131 ± 41 μg/m2. The total dust deposition over the 4-month measuring period ranged from 237 to 2935 μg/m2.